SAT0643-HPR NURSE-LED CARE FROM THE PERSPECTIVE OF PEOPLE WITH EARLY RHEUMATOID ARTHRITIS: A QUALITATIVE SYSTEMATIC REVIEW. (2nd June 2020) - Sweeney, A. M. T.; Mccabe, C.; Flurey, C.; Robson, J.; Berry, A.; Richards, P.; Ndosi, M.
Abstract : Background: Nurse-led care has been shown to be clinically effective and cost effective in rheumatoid arthritis (RA) but the role of the nurse in early RA is not well defined. Evidence for processes of care in RA is limited and it is not known how well rheumatology nurse-led clinics meet care needs of people with early RA. Objectives: The aim of this study was to develop an understanding of rheumatology nurse-led care from the perspective of people with early RA. Methods: A qualitative systematic review was conducted. The review protocol is published in the International prospective register of systematic reviews. In March 2019, the following databases were searched: MEDLINE, EMBASE, CINAHL, PsycINFO and OpenGrey. Due to lack of studies in early RA this review included adults with early and established inflammatory arthritis, qualitative studies with data on patients' perspectives of nurse-led care, published in peer-reviewed journals in English between 2010 and 2019. Two reviewers screened titles, abstracts and full texts. Data were extracted and managed in tables. Joanna Briggs Institute Critical Appraisal Checklist was used for quality assessment of the included studies. A thematic synthesis was undertaken using the framework of Thomas and Harden. 1 Results: The search identified 1034 records. After screening and assessing for eligibility, 8 qualitative studies were included in the review (133 patients), 2 studies included people with early RA. Three main themes were identified (Figure 1 ). Providing knowledge and skill . This theme delineated rheumatology nursing as providing professional expertise in the planning and delivery of care. The rheumatology nurse-led service included easy access via telephone helpline, consultations with the clinical nurse specialist for assessment of disease activity and care needs, planning of care, disease information and education, supporting self-management, and referral to rheumatologist and the multi-disciplinary team. People with RA highly valued the nurse expertise and specialist knowledge provided at nurse-led clinics. 'She was very good at informing me, so I have only praise for this ... because I have never had it like this before'. (Person with early RA). Using a person-centred approach. This theme showed nurse-led care using a person-centred approach combined with empathy and good communication skills, which created a good therapeutic environment. People with RA appreciated the person-centeredness, empathy and involvement of the nurse. ' She is very sensitive. She can see if I am feeling bad and comes straight to me and asks: "How are you today?" ...You are treated and taken seriously'. (Person with early RA). Meeting patients' care needs . This theme presented nurse-led care as creating a sense of being empowered and psychologically supported in the management of RA and its impact. Nurse-led care made people with RA feel cared for, secure and confident. It added value to rheumatology care and made care complete. 'The thought of sticking a needle into my own stomach... it felt a bit like I would never manage to do that. However, they have been absolutely wonderful here ... and now I can do it myself'. (Person with early RA). Conclusion: Nurse-led care for people with RA is characterised by provision of rheumatology expertise using a person-centred approach, and patients' holistic care needs are being met. This study found a dearth of literature on perceptions of nurse-led care in people with early RA, which highlights the need for further research in this population. References: [1]Thomas J, Harden A. Methods for the thematic synthesis of qualitative research in systematic reviews. BMC Med Res Methodol 2008; 8: 45. Disclosure of Interests: Anne-Marie Tetsche Sweeney: None declared, Candy McCabe: None declared, Caroline Flurey: None declared, Joanna Robson: None declared, Alice Berry: None declared, Pamela Richards: None declared, Mwidimi Ndosi Grant/research support from: Bristol Myers Squibb, Consultant of: Janssen, Pfizer